Efficiency and Price Effects of Mergers in European Union's Trade and Manufacturing Sectors - JELIĆ, Ozana NADOVEZA; DRUŽIĆ, Marko (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019DO - 10.14505//jarle.v10.4(42).02, 2019)
There are two basic tendencies operating simultaneously in every merger case: i) welfare gains due to efficiency related price reductions and ii) welfare losses associated with rising market power and resulting higher prices for consumers. The question of which will prevail is theoretically ambiguous, and consequently has to be settled empirically. The main objectives of this paper are to explore the effects of mergers on efficiency of consolidated firms, and to study their effects on prices in the trade and manufacturing sectors. To explore the effects of mergers on efficiency and prices we employ both a micro and macro approach by relying on firm-level data in the analysis of efficiency effects and on national-level data in the evaluation of price effects of mergers by using the Difference-in-Difference (DiD) approach on a sample of merger cases regulated by the European Commission (EC) during the 2010-2013 period. The DiD based results show that consolidated firms performed better than their competitors in the second year following the merger. Estimated efficiency gains seem to be led by efficiency growth of merged firms in the manufacturing sector. At the same time, we find evidence that compared to their unaffected counterparts, countries and economic activities in which the consolidation took place experienced a higher associated inflation in the year of the merger. Therefore, our results suggest that price effects unfold in the year when the merger is realized while efficiency effects occur with a delay of two years.